2016
DOI: 10.1093/ageing/afw144
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Japanese aged care: the pursuit of optimal health and cultural engagement

Abstract: Japan is a super-ageing society that faces pressures on its aged care system from a growing population of older adults. Naturalistic observations were undertaken at eight aged care facilities in central and northern Japan to explore how aged care is configured. Four aspects of contemporary provision were identified that offer potential gains in quality of life and health. The Japanese government mandates that aged care facilities must employ a qualified nutritionist to oversee meal preparation, fostering optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Losses in taste and smell that occur with ageing can lead to poor appetite, inappropriate food choices, as well as decreased energy consumption, which associated with impaired protein and micronutrient status that may induce subclinical deficiencies that directly impact function . There are global variations in the nutritional care and support provided to older adults to address taste‐related losses . Palatal coverage is often a matter of argument in the literature concerning the sensation of taste.…”
Section: Factors Affecting Taste Sensation In Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Losses in taste and smell that occur with ageing can lead to poor appetite, inappropriate food choices, as well as decreased energy consumption, which associated with impaired protein and micronutrient status that may induce subclinical deficiencies that directly impact function . There are global variations in the nutritional care and support provided to older adults to address taste‐related losses . Palatal coverage is often a matter of argument in the literature concerning the sensation of taste.…”
Section: Factors Affecting Taste Sensation In Older Adultsmentioning
confidence: 99%
“…Additionally, decreased taste sensitivity was observed in hospitalised older people potentially due to advanced age, polypharmacy and poor nutrition . Even though the Japanese are comparably well controlled by governmental mandate in aged care facilities , institutionalisation of older adults can also lead to nutritional deficiency if nutrient intake is not well managed or taste sensation issues are not properly evaluated. As asserted to previously, differences have been noted in the nutritional oversight provided to older adults in institutional settings around the world.…”
Section: Behavioural Specificities and Taste Sensation In Older Adultsmentioning
confidence: 99%
“…There is also variability in how aged care systems operate between countries which affects staffing structures. Japan has a national long‐term care insurance scheme and mandated staff‐to‐resident ratios of 1:3, but the type of staff varies (average reported staffing mix: 16% RNs, 35% care staff, 7% therapists/dietitians/nutritionists and 42% non‐clinical staff) . Arguably, this ratio is only possible with the Japanese long‐term care insurance scheme, but a systematic review suggested increasing staff‐to‐resident ratios or additional staff training may offer potential cost savings over time from a societal perspective by reducing health‐care costs .…”
Section: Introductionmentioning
confidence: 99%
“…Annear et al 14 1) The level of cultural engagement was greater in those who had a stronger cultural identity.…”
Section: Resultsmentioning
confidence: 99%